9x2 + 12x + 4
= 9x2 + 6x + 6x + 4
= 3x(3x + 2) + 2(3x + 2)
= (3x + 2)(3x + 2)
= (3x + 2)2
Chat with our AI personalities
2(3x^2 + 6x + 2)
(x - 8)(x - 4)
The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)
While it is possible to factor 3x2 from both of these and get 3x2(4 - 1), it's a lot easier to subtract 3x2 from 12x2 and get 9x2
If the question could more exactly be phrased as, "What is the value of x when 9x2 - 16 = 0", the answer is, x = 4 or -4. This answer can be found by factoring 9x2 - 16 into (3x + 4)(3x - 4) and setting each factor equal to zero.